Site speci fic nitrogen incorporation in reduced graphene oxide using imidazole as a novel reducing agent for ef ficient oxygen reduction reaction and improved supercapacitive performance - Roy, Dipayan; Sarkar, Saikat; Bhattacharjee, Kaustav; Panigrahi, Karamjyoti; Das, Bikram Kumar; Sardar, Kausik; Sarkar, Sourav; Chattopadhyay, Kalyan Kumar (Carbon, 2020)

Unraveling the role of excess ligand in nanoparticle pattern formation from an evaporatively dewetting nanofluid droplet - Bhattacharjee, Kaustav; Biswas, Korak; Bhagavatula L. V. Prasad (Journal of Physical Chemistry C, 2020)
Nanoparticle (NP) patterning on a solid surface via nanofluid droplet evaporation is one of the most fascinating topics of research. Quite intriguingly, though a dose of excess ligand has been invariably included in all of the experimental studies that resulted in large-area NP patterns, the role of this excess ligand has been addressed inadequately in the modeling studies carried out so far. Addressing this, we have conducted systematic studies by including excess ligand both in our experiments and modeling, and correlated the results with each other. For this, we prepared nearly monodispersed thiol-protected gold nanoparticle dispersion in toluene and added calculated amounts of excess thiol before drop-casting it onto a transmission electron microscopy (TEM) grid. Subsequently, upon solvent evaporation, the patterns formed were imaged using conventional electron microscopy and analyzed with customized image processing tools, to perform statistically significant measurements. Our study demonstrates the ability of soluble excess ligand to induce NP aggregation under nonequilibrium condition, leading to large-area monolayer formation. These experimental results were then rationalized by Monte Carlo simulations, based on a modified coarse-grained two-dimensional (2D) lattice-gas model. We found that excess ligand facilitates NP spinodal phase separation under nonequilibrium conditions, largely governed by the interplay between ligand-solvent and nanoparticle-ligand interactions. Using power spectrum density analysis, we clearly demonstrate that these spatial patterns have fractal surface characteristics due to persistent fractional Brownian motion within subdiffusion limit.

Surface functionalization of inorganic nanoparticles with ligands: a necessary step for their utility - Bhattacharjee, Kaustav; Prasad, Bhagavatula L. V. (Chemical Society Reviews, 2023)
The importance of organic ligands in protecting inorganic nanoparticles and thus imparting the needed stabilization as colloidal dispersions was realised many years ago. Currently, the rational preparation of such nanoparticles with designed organic molecules/ligands resulting in the formation of functional nanoparticles (FNPs) that are tuned for a specific application is an area of immense research interest. The preparation of such FNPs for a desired application requires a clear understanding of the interactions at the nanoparticle (NP)-ligand and ligand-solvent interfaces, and demands a deep appreciation of the surface science and coordination chemistry. In this tutorial review, we briefly explore the evolution of surface-ligand chemistry and inform the readers that, apart from protecting the surface, ligands can modulate the physico-chemical properties of the underlying inorganic NPs as well. This review further presents the design principles for the rational preparation of such FNPs, where one or more ligand shells can be added to the nanoparticle surface, thereby improving the adaptability and amenability of the NP exterior towards the environment in which they are present, as required for a specific application.

Topological phases in nanoparticle monolayers: can crystalline, hexatic, and isotropic-fluid phases coexist in the same monolayer? - Bhattacharjee, Kaustav; Vaidya, Salil S.; Pathak, Tushar; Shimpi, Jayesh R.; Prasad, Bhagavatula L. V. (Soft Matter, 2023)
Topological phases are stable configurations of matter in 2-dimensions (2D) formed via spontaneous symmetry breaking. These play a crucial role in determining the system properties. Though a number of fundamental studies on topological phase transitions and topological defect dynamics have been conducted with model colloidal systems (typically microns in size), the same is lacking on nanoparticle monolayers (NPMLs, typically made of ligand-coated sub-ten nanometer particles). Here, we show that in an evaporation-driven self-assembly process, the three topological phases, namely crystalline, hexatic, and isotropic-fluid phases, can coexist within the same NPML. We associate this coexistence with the local variation in particle size, which can be described by a unique frequency parameter (p(25)), quantifying the fraction of NPs that has size deviation greater than or equal to 25% of the mean size (where the deviation,f is defined as f = ((|Size-mean|)/mean)). The p(25)-values for the three phases are distinctly different: crystalline arrangement occurs when p(25) < similar to 0.02, while a hexatic phase exists for 0.02 <= p(25) <= 0.1. For p(25) Z 0.1, the isotropic-fluid phase occurs. Following KTHNY-theory, we further numerically extrapolate the occurrence of each phase to the accumulated excess planar strain in the NPML due to the presence of various topological defects in the structures.